Factors Influencing the Filing of Complaints, Their Investigation, and Subsequent Legal Judgment in Cases of Sexual Assault. Issue 4 (17th December 2018) - La Harpe, Romano; Burkhardt, Sandra; Ricard‐Gauthier, Dominique; Poncet, Antoine; Yaron, Michal; Fracasso, Tony
Abstract: In Geneva, examination of victims of sexual assault is performed by a gynecologist and a medical examiner. 48% of the victims file a complaint and we wanted to investigate the factors leading to file a complaint, those leading the Prosecutor to go to trial, and those influencing a conviction. Between 2006 and 2012, 676 victims of sexual assault were investigated (averaged age 26 year, mean 22). Information on injuries, perpetrators, and circumstances of the assault was collected and analyzed. The attacker being the ex‐spouse or a friend and the presence of semen were factors leading to file a complaint. The assailant being a family member or ex‐spouse and the presence of genital/anal lesions were factors influencing the Prosecutor. The presence of nongenital lesions, the assailant being known by the victim, influenced conviction. This study shows that the medical examiner plays a vital role in the investigation of cases of sexual assault.